Nursing Students’ Attitudes towards Caring for Dying Patients - A'la, Muhamad Zulfatul; Setioputro, Baskoro; Kurniawan, Dicky Endrian (Department of Nursing, Faculty of Medicine, Diponegoro University, 2018)
Background: Dying is a normal human phenomenon that requires a holistic care approach. Nurses’ attitudes towards the care for dying patients need to be explored, understood, and analyzed to improve the quality of care in palliative setting, including in nursing students.Purpose: This study explored the nursing students’ attitude and its relationship with the students’ demographic profile in caring for the dying patients in Indonesia.Methods: This study used a quantitative descriptive cross-sectional research design. The samples were 192 nursing students from Universitas Jember, Indonesia, who were recruited by using simple random sampling. Data were collected using the Frommelt Attitudes towards the Care of the Dying Care Form B Indonesian version (FATCOD-BI). The reliability test of FATCOD-BI showed a Cronbach’s alpha of 0.68, and the result of validity test using correlation coefficient showed the range of -0.278 to 0.544. Data were analyzed using frequency distribution, and mean differences test using t-test and One-Way Analysis of Variance (ANOVA).Results: Results showed that the mean of nursing students’ attitudes in caring for dying patients was 93.83±5.96 (range 30-120). Gender and training experiences had no relationship with students’ attitudes in caring for dying patients (p=0.22 and p=0.943). There was a relationship between the experiences and student academic level and the students’ attitudes in caring for dying patients (p=0.023 and p=0.036). The students’ experiences and academic level become a primary factor in the attitudes toward caring for dying patients.Conclusion: Findings revealed that student nurses’ attitudes in caring for dying patients was in low category and there was no significant relationship between gender and training experience and students’ attitudes towards caring for the dying patients. In contrast, experiences in caring for dying patients and academic level were associated with students’ attitudes. Further studies in the development of curriculum on dying patient care emphasizing on socio-demographic status are recommended.